Fibromyalgia in Iraqi patients with asthma and its impact on asthma severity and control - Gorial, Faiq I. (Ann Med Surg (Lond), 2020)
BACKGROUND: Fibromyalgia (FM) is common with significant impact on patients quality of life. Limited reports on coexistence of FM with asthma. OBJECTIVES: To assess the prevalence of FM in asthmatic patients and its impact on asthma severity and control. PATIENTS AND METHODS: This case-control study included 103 patients with asthma and 102 apparently healthy controls matched in age and sex. Sociodemographic and clinical characteristics of FM and controls were recorded. FM was diagnosed according to the 2016 revision of American College of Rheumatology criteria. Asthma diagnosis and severity were performed by the pulmonologist according to Global Initiative for Asthma (GINA) guidelines and asthma control was assessed by Asthma Control Test (ACT) score. RESULTS: The mean age of asthmatic patients was 41.1 ± 12.7 years and for controls was 39.8 ± 12 years (p = 0.453). Females were more prevalent in asthmatic patients and controls although statistically were not significant (p-value = 0.532). Prevalence of FM was significantly more in asthmatic patients compared to controls [18 (17.6%) vs 7 (6.8%), p = 0.018] and asthmatic patients had three folds risk of having FM (ranging from 1.2 to 7.4 times. FM increased the risk of severe asthma by 4.91 folds (P < 0.005). Also, only FMS and glucocorticoids were significant independent predictor of having poor asthma control. FM was significantly and negatively correlated with low ACT score (β standardized regression coefficient = −0.291, p = 0.005). CONCLUSIONS: fibromyalgia was common in asthmatic patients and was significantly associated with more severe and poorly controlled asthma.